2020
DOI: 10.4102/curationis.v43i1.2129
|View full text |Cite
|
Sign up to set email alerts
|

Nurse managers experiences of their leadership roles in a specific mining primary healthcare service in the West Rand

Abstract: Background Nurse managers are leaders in mining primary healthcare. Their leadership roles include inspiring and empowering operational managers and nursing personnel, by leading with competence developing them to become followers with insight and direction. However, these leadership roles are not clearly defined, and are negatively influenced by the traditional mining leadership style. Objectives The aim of this study was to explore and describe the nurse managers’ exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…Tingvoll, Saeterstrand and McClusky ( 2016 ) and Masters ( 2017 ) reported that leadership roles are increasing and cannot be achieved using inherent policies that cannot be challenged, and that is not recognising all the relevant stakeholders. The leadership role of a nurse manager in primary healthcare is to develop and update policies to ensure relevance in practice and to eradicate role ambiguity and delays that may arise from the use of incongruent policies (Jooste 2017 ; Nene et al 2020 ). Nurcahyo et al ( 2018 ) attest that the use of incongruent policies is a challenge, because they inhibit the engagement of nurse managers for the success of the organisation.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tingvoll, Saeterstrand and McClusky ( 2016 ) and Masters ( 2017 ) reported that leadership roles are increasing and cannot be achieved using inherent policies that cannot be challenged, and that is not recognising all the relevant stakeholders. The leadership role of a nurse manager in primary healthcare is to develop and update policies to ensure relevance in practice and to eradicate role ambiguity and delays that may arise from the use of incongruent policies (Jooste 2017 ; Nene et al 2020 ). Nurcahyo et al ( 2018 ) attest that the use of incongruent policies is a challenge, because they inhibit the engagement of nurse managers for the success of the organisation.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Nurse managers face challenges in leadership roles in a mining primary healthcare setting in South Africa. Banaeianjahromi and Smolander ( 2017 ) and Nene et al ( 2020 ) confirmed that these challenges experienced by nurse managers in a mining primary healthcare setting include lack of effective communication, bureaucratic mining management and union influence. Primary healthcare is a frontline service that manages the health problems at this level for all the mine workers.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The study of the activities under the competence of the nurse also made it possible to find that the groups of participants do not understand well the role of the nurse within the nursing team and in the health care services, considering that essential assistance needs, which are not private and can be delegated, were mentioned the most. Although all nursing activities are part of the competence of nurses (7) , in regard to the social division of labor, these professionals are the leaders of the nursing team (36) . They are responsible for higher complexity assistance activities (7,10,36) , not to mention their managerial, administrative, educational and research-related competences (12,37) .…”
Section: Discussionmentioning
confidence: 99%
“…Although all nursing activities are part of the competence of nurses (7) , in regard to the social division of labor, these professionals are the leaders of the nursing team (36) . They are responsible for higher complexity assistance activities (7,10,36) , not to mention their managerial, administrative, educational and research-related competences (12,37) .…”
Section: Discussionmentioning
confidence: 99%